Development And Evaluation Of Customized Pes Planus Orthotic Insole Using Additive Manufacturing - Mohamad, Azlinda (2019)
Pes planus (also known as flat feet) orthotic insole designed to support, correct the deformities and improve the movement of joints or limbs. The custom orthotic insole can fit the patient’s body and perform better than off-the-shelf insoles. Due to the large range of dimensions characteristic for each individual, a mass production is not suitable for the custom insole productions. For this reason, it is necessary to consider another approach, such as additive manufacturing. The purpose of this study is to develop a personal orthotic Pes Planus insole using Fused Deposition Modeling (FDM). Customized fabrication of orthotic insole using FDM has been through six main steps: Pes Planus feet screening, 3D scanning of the anatomic surface, feet 3D surface reconstruction and modification, insole 3D modeling and converting to STL format and finally fabricating using FDM machine. Evaluation by a medical practitioner was conducted at the end of the study for the purpose of obtaining feedback from the expert and ensuring the insole's ability to correct Pes Planus feet. The most suitable material in the insole production is TPU. This technique will contribute to better orthotic planus insole in terms of reducing manufacturing time, economic and personal at the patient's foot, rather than conventional methods that need to go through the mold manufacturing process in advance.